Behavior of Precast Prestressed Concrete Segmental Beams - Al-Sherrawi, Mohannad Husain; Allawi, Abbas A.; AL-Bayati, Basim H.; Al Gharawi, Mohanned; El-Zohairy, Ayman (Civil Engineering Journal, 2018)
The structural behavior of Segmental Precast Post-tensioned Reinforced Concrete (SPPRC) beams largely depends on the behavior of the joints that connect between the segments. In this research, series of static tests were carried out to investigate the behavior of full-scale SPPRC beams with different types of epoxy-glued joint configurations; multi-key joint, single key, and plain key joint. The reference specimen was monolithically casted beam and the other specimens were segmental beams with five segments for each one. The general theme from the experimental results reflects an approximate similarity in the behavior of the four beams with slight differences. Due to the high tensile strength of the used epoxy in comparison to concrete, cracks at joints occurred in the concrete cover which was attached to the epoxy mortar.